Perancangan User Interface/User Experience Aplikasi Tiket Online Pendakian Berbasis Android Pada (Bukit Anak Dara) - Maulana A, Rizal; rosika, herliana; Saputra, Joni (SainsTech Innovation Journal, 2023)
Abstract: Purchasing climbing tickets at Anak Dara Hills is still manual, making it difficult for climbers who are outside the area to book tickets or find information regarding climbing conditions on Anak Dara Hills. Based on the above problems, it is necessary to design a user interface / user experience for an android-based online climbing ticket using the cognitive walkthrough method, this method uses 5 participants as material to find information or conduct usability trials. Based on the results of the analysis and observation, a prototype design was made. Then a trial was conducted on the five participants. After testing the prototype, the five participants were very satisfied with the application design and prototype that was easy to understand. Abstrak: Pembelian tiket pendakian di bukit anak dara tergolong masih manual, sehingga menyulitkan bagi para pendaki yang berada di luar daerah untuk melakukan pemesanan tiket maupun mencari informasi terkait kondisi pendakian di bukit anak dara. Berdasarkan masalah diatas maka dibutuhkan perancangan user interface/user experience tiket online pendakian berbasis android dengan menggunakan metode cognitive walkthrough, metode ini menggunakan 5 responden sebagai bahan untuk mencari informasi ataupun melakukan uji coba usability. Berdasarkan hasil analisis dan observasi maka dibuat rancangan prototype. Kemudian dilakukan uji coba kepada kelima responden. Setelah melakukan uji coba protoype kelima responden sangat puas terhadap desain aplikasi dan prototype yang mudah dipahami.